The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1126/science.296.5568.727
|View full text |Cite
|
Sign up to set email alerts
|

Global Cooling After the Eruption of Mount Pinatubo: A Test of Climate Feedback by Water Vapor

Abstract: The sensitivity of Earth's climate to an external radiative forcing depends critically on the response of water vapor. We use the global cooling and drying of the atmosphere that was observed after the eruption of Mount Pinatubo to test model predictions of the climate feedback from water vapor. Here, we first highlight the success of the model in reproducing the observed drying after the volcanic eruption. Then, by comparing model simulations with and without water vapor feedback, we demonstrate the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
350
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 455 publications
(396 citation statements)
references
References 35 publications
42
350
3
1
Order By: Relevance
“…The close correspondence between average l q RH and l q arises despite the fact that the atmosphere does not actually keep RH fixed, but displays a complex pattern of increases and decreases. Soden et al [2002Soden et al [ , 2005 analyzed the LW feedback and concluded that it has a magnitude close to that of a constant-RH feedback, and Soden and Held [2006] concluded that l q and l q RH differed in climate models by just a few percent. [19] Figures 4a-4d show that the LW water-vapor feedback arises primarily from changes in q in the tropical upper troposphere, while the SW feedback arises from changes in the lower troposphere.…”
Section: Strength Of the Water-vapor Feedbackmentioning
confidence: 99%
“…The close correspondence between average l q RH and l q arises despite the fact that the atmosphere does not actually keep RH fixed, but displays a complex pattern of increases and decreases. Soden et al [2002Soden et al [ , 2005 analyzed the LW feedback and concluded that it has a magnitude close to that of a constant-RH feedback, and Soden and Held [2006] concluded that l q and l q RH differed in climate models by just a few percent. [19] Figures 4a-4d show that the LW water-vapor feedback arises primarily from changes in q in the tropical upper troposphere, while the SW feedback arises from changes in the lower troposphere.…”
Section: Strength Of the Water-vapor Feedbackmentioning
confidence: 99%
“…A theoretically well-determined value is the change in waterholding capacity of the atmosphere of 7%/K, governed by the Clausius-Clapeyron equation [1]. This equation indicates an increase of precipitable water (column-integrated water) in relation to the constant relative humidity on the global scale [12]. This value is at odds with the model-predicted increase of 2%/K in precipitation intensity proposed in a study using an ensemble of 17 latest-generation climate models [13].…”
mentioning
confidence: 99%
“…Heat Content Anomaly/10 22 J f0055 FIGURE 10 The global and ensemble mean ocean heat content (10 22 J) anomaly for 300 m and whole depth ocean for the Pinatubo ensemble calculated with respect to ensemble control.…”
Section: P0200mentioning
confidence: 99%
“…Volcanically induced changes in interior ocean temperature, the meridional overturning circulation and steric height have even longer relaxation times, from several decades to a century. Because of their various impacts on climate systems, volcanic eruptions play a role of natural tests, providing an independent means of assessing multiple climate feedback mechanisms and climate sensitivity [7][8][9][10][11]. p0030…”
Section: P0020mentioning
confidence: 99%